Effects of Sodium Oleate and Ultrasonic Pre-treatment on the Grinding of Vanadium-titanomagnetite - Yufeng ZHOU; Gongming QIAN; Qing YE; Xinke LING; Jun XIE (Kuangchan zonghe liyong)
This is an article in the field of mineral processing engineering. With vanadium-titanomagnetite (VTM) from Panxi as the investigation object, the effects of sodium oleate and ultrasonic pre-treatment on grinding and separation were studied. The particle size, Zeta potential, morphology, dispersion, surface elements and adsorption characteristics of grinding products were measured and analyzed to explore the influence and mechanism of ultrasonicand sodium oleate on grinding process of VTM. The results showed that the yield with size of -0.074 mm of grinding products increased by 3.37% when sodium oleate was added 1 000 g/t. The yield with size of -0.074 mm of grinding products increased by 4.19% after ultrasonic pretreatment and grinding with sodium oleate. In the grinding progress, sodium oleate is chemically adsorbed on the surface of VTM to reduce the mineral surface hardness. Ultrasonic pre-treatment can clean the mineral surface and expose more adsorption sites. Moreover, part of Fe2+ on the mineral surface can be oxidized to Fe3+, which is conducive to the adsorption of sodium oleate. It is demonstrated that sodium oleate addition and ultrasonic pre-treatment can effectively improve the grinding efficiency of VTM.